The role of serum IL-6 in colorectal cancer patients and it’s relationship with serum CEA level - Al-Ghurabi, Batool H.; Al-Saady, Luma G.; Al-Hassan, Ahmed A. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: The role of cytokines in cancer immunity and carcinogenesis in general has been well established, which play an important role in pathogenesis of many solid cancer. This study aimed to shed light on the possible role of IL-6 in pathogenesis of CRC and its relationship with serum CEA level.Patients and methods: This study covered 50subjects. It comprised of 30 patients with CRC, compared with 20 healthy normal controls. Serum IL-6 and CEA analysis were performed by ELISA.Results: This study revealed a significant elevation in serum IL-6 level among CRC patients (16.2 pg/ml) in comparison to that of healthy control (4.8 pg/ml) (p